Aspecten hedendaagse fotografie. - Bokhoven, J.E. (Schiedam : Stedelijk Museum Schiedam, 1979)
van den Boom, Herman ; van Denderen, Ad ; den Hollander, Paul ; de Nooijer, Paul ; Schröter, Hans J. ; Zwart, Jan ; Bien, Ania ; Eykelboom, Hans ; Hoover, Nan ; Hooykaas, Madelon ; Stansfield, Elsa ; de Kroon, Harrie ; Urban, Nikolaus
Aspecten hedendaagse fotografie, Stedelijk Museum Schiedam, 9 juni 1979 t/m 22 juli 1979
boek